Drosophila Peptide Hormones Allatostatin A and Diuretic Hormone 31 Exhibiting Complementary Gradient Distribution in Posterior Midgut Antagonistically Regulate Midgut Senescence and Adult Lifespan. - Takeda, K.; Okumura, T.; Terahata, M.; Yamaguchi, M.; Taniguchi, K.; Adachi-Yamada, T. (Zoological Science (Zoological Society of Japan), 2018)
Enteroendocrine cells (EEs) are evolutionarily conserved gastrointestinal secretory cells that show scattered distribution in the intestinal epithelium. These cells classified into several subtypes based on the hormones they produce in both mammals and insects. In the fruit fly Drosophila, it has been suggested that nearly equal numbers of two subtypes of EEs (Allatostatin A: AstA and Diuretic hormone 31 : Dh31) are alternately produced from the intestinal stem cells in the posterior midgut. However, we found that these two subtypes are not always present in this manner, but are rather distributed in a complementary frequency gradient along the posterior midgut. We show that midgut-preferential RNA knockdown of the peptide hormones AstA or Dh31 respectively results in decreased or increased adult lifespan. This effect on longevity is apparently correlated with the midgut senescence phenotypes as a result of direct hormone action through both hormone receptors expressed in the enteroblasts or other midgut cell types. However, gut senescence does not appear to be the direct cause for longevity regulation, as knockdown of both hormone receptors did not affect adult lifespan. Furthermore, these senescence phenotypes appear to be independent of insulin signaling and manifest in an organ-specific manner. These results indicate that the two intestinal secretory peptides antagonistically regulate adult lifespan and intestinal senescence through multiple pathways, irrespective of insulin, which implicates a complementary gradient distribution of each of the hormone-producing EEs, consistent with local requirements for cell activity along the posterior midgut.